What we think we know: Knowledge transfer between actors in a construction project - Bustamante Molina, Isabel; Kauffeldt, Oscar (My University, 2022)
Over the last decades, attention to the creation and maintenance of knowledge in the construction industry has increased. The fields of knowledge management and organizational learning have shed light on how knowledge is transferred between different projects. Far less attention has been put towards solving the issue of transferring knowledge between different phases and agents within the same project. In the complex setting of construction projects, with its interdependent stakeholders, the type of knowledge needed varies wildly depending on the project phase. Understanding needs to be shared in order to align project participants’ work and move towards the project’s goals. To do this, we must study what happens to knowledge within projects. This thesis takes a critical look at the creation, transformation, and transfer of knowledge within construction projects, to identify how and why knowledge is lost. It is an exploration of what happens to knowledge when the project transitions from early to detailed design. It looks at the interaction between actors with different perspectives, disciplines, and interests, and over a long-time span. The thesis draws rich data from a case project, using project documentation to frame the project’s knowledge infrastructure and an interview study to complement it. Our findings show three mechanisms affecting knowledge loss in construction projects. First, that different perspectives among project participants are linked to misunderstanding. Second, that project changes inflict losses by overwriting previous design ideas. Changes are nearly inevitable, as requirements and personnel are changed, and, as such, the project must be flexible and adaptable to lessen knowledge loss. And third, that the reasoning behind decision making carries actionable knowledge, and a failure to document or otherwise transfer this knowledge can have severe implications during redesign and implementation of design changes. By analyzing why knowledge is lost, the thesis contributes with new insights into the driving forces behind knowledge loss within construction projects.
Keywords: Holistic framework of knowledge management; Knowledge creation; Knowledge transfer; Knowledge transformation; Project knowledge management; Shared understanding